Highly Efficient Near-Infrared Light-Emitting Diodes Based on Chloride Treated CdTe/CdSe Type-II Quantum Dots - Feng, Huwei; Song, Jiaojiao; Song, Bin; Lin, Qingli; Shen, Huaibin; Li, Lin Song; Wang, Hongzhe; Du, Zuliang (Frontiers in Chemistry, 2020)
Quantum dot light-emitting diodes (QLEDs) have been considered as the most promising candidate of light sources for the new generation display and solid-state lighting applications. Especially, the performance of visible QLEDs based on II-VI quantum dots (QDs) has satisfied the requirements of the above applications. However, the optoelectronic properties of the corresponding near-infrared (NIR) QLEDs still lag far behind the visible ones. Here, we demonstrated the highly efficient NIR QLEDs based on chloride treated CdTe/CdSe type-II QDs. The maximum radiant emittance and peak external quantum efficiency (EQE) increased by 24.5% and 26.3%, up to 66 mW/cm2 and 7.2% for the corresponding devices based on the chloride treated CdTe/CdSe QDs with the PL peak located at 788 nm, respectively, compared with those of devices before chloride treatment. Remarkably, the EQE of > 5% can be sustained at the current density of 0.3~250 mA/cm2 after the chloride treatment. Compared with NIR LEDs based on transition metal complex, the efficiency roll-off has been suppressed to some extent for chloride treated CdTe/CdSe based NIR QLEDs. Based on the optimized conditions, the peak EQE of 7.4%, 5.0% and 1.8% can be obtained for other devices based on chloride treated CdTe/CdSe with PL peak of 744, 852 and 910 nm, respectively. This improved performance can be mainly attributed to the chloride surface ligand that not only increases the carrier mobility and reduces the carrier accumulation, but also increases the probability of electron-hole radiative efficiency within QD layers.